Pemanfaatan Meja Stainless Sebagai Media Penjemuran Udang Kasia Bagi Masyarakat Kampung Arar Kabupaten Sorong - Sulfiana, Sulfiana; Ibal, La; Abu, Nur; Rahmi, Rahmi; Rahayu, Andi; Murni, Murni; Arifin, Herlina; Rian Histiariani, Aprisa; Salmawati, Salmawati (Jurnal Pengabdian kepada Masyarakat Nusantara, 2024)
Arar Village, located in Sorong Regency, has abundant marine resource potential, especially in the catch of cassia shrimp. However, the cassia shrimp processing process still faces obstacles, especially in the drying stage, which is carried out traditionally, thus affecting the quality of the product. This study aims to improve the quality and cleanliness of cassia shrimp processed products through the application of stainless steel drying tables. The implementation method of this community service is carried out in three stages, namely preparation, implementation, and the final stage. The preparation stage involves coordination with the local government, situation analysis, and identification of community needs. At the implementation stage, education and training are carried out on the use of stainless steel drying tables, as well as direct practice simulations for the community. The final stage involves evaluating activities through questionnaires and interviews to measure the success of the training. The results of the community service show that the use of stainless steel drying tables improves the quality of cassia shrimp by maintaining cleanliness, reducing bacterial contamination, and extending shelf life. In addition, this training increases community knowledge about the importance of using hygienic tools in fisheries processing. In the future, it is hoped that this technology can be widely accepted by the Arar Village community to support increased productivity and more sustainable fisheries-based economic welfare.